Development of ICT Exam Document Validation System - Avila, Jennifer; Villafuerte, Ritchell (International Journal of Sustainability and Advanced Integrated Research, 2026)
The increasing number of applicants for the ICT Proficiency Examination has created significant challenges for the Department of Information and Communications Technology (DICT) Region VIII, particularly in the manual verification of examination requirements. Traditional validation procedures are often time-consuming, prone to data-entry mistakes, and susceptible to inconsistencies in decision-making. To address these concerns, this study developed an ICT Exam Validation System that automates the verification and assessment of applicant documents.  The system was developed using the Agile System Development Life Cycle, which involved iterative phases of planning, design, development, testing, deployment, and evaluation. It features dedicated portals for applicants and administrators, secure user authentication, automated document validation, and real-time notification capabilities. To determine its effectiveness, the system underwent functional and technical evaluations based on reliability measures and the ISO/IEC 25059:2023 quality model, focusing on key attributes such as adaptability, reliability, transparency, and operational efficiency.  The evaluation results indicate that the system provides a dependable and practical solution for streamlining the validation of ICT Proficiency Examination requirements. By reducing manual intervention and improving the consistency of validation decisions, the system enhances the overall efficiency of examination administration. Moreover, the project contributes to the advancement of digital governance initiatives by supporting innovation in public service delivery and promoting the modernization of government processes. The study also aligns with Sustainable Development Goals (SDGs) 9 and 16 by encouraging the adoption of intelligent technologies that strengthen institutional effectiveness, improve service accessibility, and foster sustainable digital transformation in the public sector.
Keywords: Agile System Development Life Cycle; Document Validation; E-Governance; ICT Proficiency Examination; Intelligent Automation; Web-Based System